Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense—24. Odontocheila paraexcisipenis sp. nov., a new species of the O. cajennensis species-group (Coleoptera: Cicindelidae) - Moravec, Jiří; Huber, Ronald (Zootaxa, 2021)
A new species of the genus Odontocheila Laporte de Castelnau, 1834 is described from Venezuela as Odontocheila paraexcisipenis sp. nov. It is classified as a further species of the large O. cajennensis species-group and described subsequent to the recently published revision of the genus (Moravec (2018). Illustrations of the habitus, diagnostic characters and variability of the new species and distinguishing characters of similar species are presented in colour photographs. Revised key to species of the O. cajennensis species-group is presented with references to descriptions and illustrations of other species of the species-group in the above-cited taxonomic revision of the genus. An essential map of distribution is also given.